High-Throughput Sequencing Reveals Further Diversity of Little Cherry Virus 1 with Implications for Diagnostics - Katsiani, Asimina; Maliogka, Varvara; Katis, Nikolaos; Svanella-Dumas, Laurence; Olmos, Antonio; Ruiz-García, Ana B.; Marais, Armelle; Faure, Chantal; Theil, Sebastien; Lotos, Leonidas; Candresse, Thierry (2019)
Little cherry virus 1 (LChV1, Velarivirus, Closteroviridae) is a widespread pathogen of sweet or sour cherry and other Prunus species, which exhibits high genetic diversity and lacks a putative efficient transmission vector. Thus far, four distinct phylogenetic clusters of LChV1 have been described, including isolates from different Prunus species. The recent application of high throughput sequencing (HTS) technologies in fruit tree virology has facilitated the acquisition of new viral genomes and the study of virus diversity. In the present work, several new LChV1 isolates from different countries were fully sequenced using different HTS approaches. Our results reveal the presence of further genetic diversity within the LChV1 species. Interestingly, mixed infections of the same sweet cherry tree with different LChV1 variants were identified for the first time. Taken together, the high intra-host and intra-species diversities of LChV1 might affect its pathogenicity and have clear implications for its accurate diagnostics.